PENGARUH LIMBAH INDUSTRI TERHADAP TINGKAT PENCEMARAN TIMBAL DI PERAIRAN SUNGAI TALLO - Muammar, Muammar; Rais, Muhammad; Patang, Patang (Jurnal Pendidikan Teknologi Pertanian, 2019)
The purpose of this study was to to determine the lead contamination and water quality in Tallo River by comparing it with standards quality of waters, to obtain information and data on the effect of industrial waste on the level of lead pollution (Pb) in the watersTallo River, and to analysis the effect of lead on water quality (temperature, pH and dissolved oxygen) in Tallo River. This research was a descriptive study using a survey method. The study was conducted by taking samples of water, soil, and fish at three different stations, namely at the Tello Bridge area, at the area around the section of the Toll Bridge and at the Port of Paotere. The results of this study indicated that lead (Pb) pollution in water, fish and soil, were still below the threshold value. This indicated that water, fish and the land of the Tallo River were still in good condition. Tallo River water quality (temperature, pH and DO), according to Government Regulation No. 82 of 2001, was categorized in the class 3 water criteria. Industrial waste on the Tallo River to Paotere Port had affected the concentration of lead in water, fish and land but has not exceeded the normal threshold. The results of linear regression test showed that effect of lead (Pb) on water temperature only 36% and the remaining 64% determined by other factors (R2= 0,3627), meaning that lead (Pb) in the Tallo River had less effect on temperature. Lead (Pb) in the Tallo River had less effect on DO parameters (R2= 0,4417). According to analysis, lead (Pb) in the Tallo River had high effect on pH parameters (R2= 0,9048).